MST1/2 Balance Immune Activation and Tolerance by Orchestrating Adhesion, Transcription, and Organelle Dynamics in Lymphocytes - Ueda, Yoshihiro; Kondo, Naoyuki; Kinashi, Tatsuo (Frontiers in Immunology, 2020)
The STE20-like serine/threonine kinases MST1 and MST2 (MST1/2) are mammalian homologs of Hippo in flies. MST1/2 regulate organ size by suppressing the transcription factor YAP, which promotes proliferation. MST1 is predominantly expressed in immune cells, where it plays distinct roles. Here, we review the functions of MST1/2 in immune cells, uncovered by a series of recent studies, and discuss the connection between MST1/2 function and immune responses. MST1/2 regulate lymphocyte development, trafficking, survival, and antigen recognition by naive T cells. MST1/2 also regulate the function of regulatory T cells and effector T cell differentiation, thus acting to balance immune activation and tolerance. Interestingly, MST1/2 elicit these functions not by the “canonical” Hippo pathway, but by the non-canonical Hippo pathway or alternative pathways. In these pathways, MST1/2 regulates cellular processes relating to immune response, such as chemotaxis, cell adhesion, immunological synapse, gene transcriptions. Recent advances in our understanding of the molecular mechanisms of these processes have revealed important roles of MST1/2 in regulating cytoskeleton remodeling, integrin activation, and vesicular transport in lymphocytes. We discuss the significance of the MST1/2 signaling in lymphocytes in the regulation of organelle dynamics.